Chapter 11: The Worker Protection Standard - Frederick Fishel; O. Norman Nesheim; Thomas W. Dean (EDIS)
The Worker Protection Standard (WPS) is a set of regulations issued by the U. S. Environmental Protection Agency (EPA). These regulations are designed to protect agricultural workers and pesitcide handlers from exposure to pesticides used in the production of agricultural plants on farms, forests, nurseries, and greenhouses. This document is P119, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.